Influence of basic catalysts on the decarboxylation kinetics of naphthenic acids - Mejía, Carlos; Quiroga, Haydée; Vásquez, Custodio; Peña, Darío (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Processing of high acidity oils causes corrosion problems in transfer pipelines and distillation units. In this work, the basicity of MgO has been increased by means of humid impregnation with alkaline earth metals. The influence on the decarboxylation reaction of a solution with mineral oil and naphthenic acids was evaluated. The process was carried out at 150, 200, 250 and 300°C and the reaction time was varied from 0 a 360 minutes. The increase in the basicity of the catalysts caused an increase in the decarboxylation reaction rate even if the superficial area of the catalyst was diminished by the superficial modification. The activation energy and the frequency factor of the catalyzed and non catalyzed reaction were determined by the kinetic study. The activation energy for the decarboxylation of naphthenic acids decreased in 45% with regard to the non catalyzed reaction. Finally, tests of catalytic decarboxylation were realized by using heavy oil at 300°C and 360 minutes. It was calculated a higher removal of naphthenic acids in the heavy oil than the removal found in the solution of mineral oil and naphthenic acids.